Korelasi Antara Pola Asuh Islami Orang Tua dengan Tingkat Kemandirian - Hofid Hofid (LPPM IAIN Sorong, 2018)
This article shows that one form of parenting in improving children's independence is deliberation by parents. Parents recognize the ability of their children, and then the child is given the opportunity to not always depend on the parents. In this case, the role of deliberation is important to reach a joint decision fairly and wisely, so that children form a creative, independent, and still respect the parents. Thus, the better parenting performed by parents, it will have a positive impact on the independence of their children